High-performance proton exchange membrane and preparation method thereof

By introducing amino-functionalized MOF nanoparticles and zirconium phosphate glass network into the proton exchange membrane, combined with a sulfonated COFS coating, the swelling and phosphoric acid loss problems of the proton exchange membrane at high temperatures were solved, achieving low swelling rate and high phosphoric acid retention rate, thus improving the performance stability of the fuel cell.

CN121097153APending Publication Date: 2025-12-09DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511163212.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-12-09

AI Technical Summary

Technical Problem

Existing proton exchange membranes are prone to swelling and phosphoric acid loss at high temperatures, which affects the performance stability of fuel cells.

Method used

A proton exchange membrane was prepared by using sulfonated polybenzimidazole as the main chain, combined with amino-functionalized MOF nanoparticles and zirconium phosphate to form a glass network structure, and then formed with a sol-gel method. A sulfonated COFS coating was formed on both sides of the membrane, followed by activation with phosphoric acid solution and gradient annealing.

Benefits of technology

It effectively inhibits high-temperature swelling, improves phosphate retention, enhances mechanical stability and proton conduction efficiency, and extends membrane lifetime.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121097153A_ABST
    Figure CN121097153A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fuel cells, in particular to a high-performance proton exchange membrane and a preparation method thereof. The proton exchange membrane prepared by the invention takes sulfonated polybenzimidazole as a main chain, MOFs nanoparticles are grafted firstly, then SPBI / ZrP-MOFs hybrid sol is formed by combining a sol-gel method with a zirconium phosphate precursor, then a three-dimensional interpenetrating structure is constructed by doping dynamic disulfide bonds and utilizing ultraviolet light to initiate a crosslinking reaction, and then the membrane is formed by a tape casting method. And finally, a sulfonated COFS coating is additionally arranged. Through organic-inorganic multiphase cooperation and process innovation, the low swelling rate, high phosphoric acid retention rate and long-term chemical stability at high temperature are achieved, and the performance bottleneck in the prior art is broken through.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of fuel cells, and more particularly to a high-performance proton exchange membrane and its preparation method. Background Technology

[0002] Proton exchange membranes (PEMs) are the core components of proton exchange membrane fuel cells (PEMFCs) and proton exchange membrane electrolysis for hydrogen production (PEMWEs), and their performance directly affects the energy conversion efficiency and long-term stability of the cells. PEMs must possess high proton conductivity, low gas permeability, excellent chemical stability, high mechanical strength, and long lifespan. Traditional perfluorosulfonic acid membranes (such as Nafion) are widely used due to their excellent proton conductivity and chemical stability; however, they are prone to swelling at high temperatures (>80°C) (swelling rate >3%), leading to a sharp drop in proton conductivity and an increase in hydrogen permeability.

[0003] Currently, improvements to high-temperature PEMs employ phosphoric acid-doped perfluorosulfonic acid membranes, which enhance high-temperature performance through the proton conduction mechanism of phosphoric acid. For example, in the paper "Phosphoric acid-sustained-release strategy boosting durability of high temperature proton exchange membrane fuel cells" published in Chemical Engineering Journal by Zhang Jialin et al., it was pointed out that during fuel cell operation, especially at high temperatures of 130-180°C, water condensation and electromigration can lead to phosphoric acid loss, thereby affecting the performance stability of the battery under a wide temperature range and high current load.

[0004] Therefore, there is an urgent need to develop a proton exchange membrane that combines low swelling rate, high phosphate retention rate, and long-term chemical stability at high temperatures, in order to overcome the performance bottlenecks of existing technologies. Summary of the Invention

[0005] The purpose of this invention is to provide a high-performance proton exchange membrane and its preparation method, which has the advantages of good high-temperature low swelling rate and high phosphate retention rate.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows: This invention provides a method for preparing a proton exchange membrane, comprising the following steps: Step 1: Dissolve sulfonated polybenzimidazole in N-methylpyrrolidone, add amino-functionalized MOF nanoparticles for grafting reaction to obtain composite solution; Step 2: The zirconium phosphate precursor solution is mixed with the composite solution obtained in Step 1 using the sol-gel method. The pH is adjusted to 1.5-2.0 with hydrochloric acid, and then adjusted to 2.5-3.0 with ammonia to form SPBI / ZrP-MOFs hybrid sol. Step 3, use the SPBI / ZrP-MOF obtained in Step 2. S The hybrid sol is cast into a film and then dried; Step 4: Form sulfonated COF on both sides of the membrane. S The coating is then dried. Step 5: The membrane obtained in Step 4 is first activated with phosphoric acid solution and then subjected to gradient annealing to obtain the proton exchange membrane.

[0007] The present invention is further configured such that step 1 specifically comprises the following steps: a) Sulfonated polybenzimidazole is dissolved in N-methylpyrrolidone to obtain a mixed solution; the concentration of sulfonated polybenzimidazole in the mixed solution is 5-15 wt%. b) Add amino-functionalized MOF to the mixed solution obtained in step a). S Nanoparticles were reacted at 30-80℃ for 6-12 hours under nitrogen protection. c) A composite solution was obtained after centrifugation; In step b), the sulfonated polybenzimidazole and amino-functionalized MOF S The mass ratio of nanoparticles is (3:1)-(10:1), and the water content of the reaction system is controlled to be <500ppm (meaning that the mass of water in the reaction system does not exceed 0.05% of the total mass of the reactants).

[0008] The present invention is further configured such that, in step a), the degree of sulfonation of the sulfonated polybenzimidazole is 30%-50%; In step b), the amino-functionalized MOF nanoparticles are selected from at least one of NH2-UiO-66 and NH2-MIL-125(Ti), and their pore size is 0.6-1.6 nm; The preparation method of NH2-UiO-66 is as follows: using zirconium salt as the metal source and 2-aminoterephthalic acid as the ligand, NH2-UiO-66 is synthesized by solvothermal reaction in DMF. The preparation method of NH2-MIL-125(Ti) is as follows: using tetraisopropyl titanate and 2-aminoterephthalic acid as raw materials, NH2-MIL-125(Ti) is synthesized by reacting in methanol solvent.

[0009] The present invention is further configured such that step 2 specifically comprises the following steps: 1) Mix ZrOCl2·8H2O and H3PO4 at a molar ratio of 1:1.25-1:3 and age for 24-48 h to obtain a zirconium phosphate precursor solution; 2) Mix the zirconium phosphate precursor solution with the composite solution obtained in step 1 at a mass ratio of sulfonated polybenzimidazole to zirconium phosphate precursor of (1:0.5)-(1:2); 3) First, add hydrochloric acid to adjust the pH to 1.5-2.0, then add ammonia to adjust the pH to 2.5-3.0, forming SPBI / ZrP-MOF. S Hybrid sol.

[0010] The present invention is further configured such that, in step 4, the sulfonated COF S The coating formation steps are as follows: A) Mix the silane coupling agent with ethanol, and add sulfonated COF. S Polyvinylpyrrolidone (PVP) was added as a dispersant, and after ultrasonic-assisted dispersion, a mixed slurry was obtained; the volume ratio of the silane coupling agent to ethanol was 1-1.5:100, and the concentration of PPVP in the mixed slurry was 0.4-0.6 wt%. B) Coat both sides of the membrane with the mixed slurry obtained in step A); C) Immerse the membrane from step B) in ethanol to remove free silane, then dry it.

[0011] The present invention is further configured such that, in step A), the sulfonated COF S The monomer is at least one of SO3H-COF-300, SA-TFP COF, and SO3H-COF-790, wherein the pore size of SA-TFP COF is 1.2-1.8 nm and the sulfonic acid group density is 1.2-2.0 mmol / g, and the pore size of SO3H-COF-300 and SO3H-COF-316 is 0.65-1.0 nm and the sulfonic acid group density is 2.8-4.2 mmol / g; SA-TFP COF, SO3H-COF-300, and SO3H-COF-316 are prepared by a solvothermal method: the monomer is reacted in NMP solvent at 120-150℃ for 24-48 h, and then SO3H groups are introduced by sulfonation with concentrated sulfuric acid; The silane coupling agent is an aminosilane.

[0012] The present invention is further configured such that, in step B), the coating thickness is 5-15 μm.

[0013] The present invention is further configured such that, in step 5, the phosphoric acid solution activation treatment is performed by immersing the obtained membrane in a phosphoric acid solution at 80-90°C for 0.5-1.5 hours, wherein the concentration of the phosphoric acid solution is 65-75 wt%.

[0014] The present invention is further configured such that, in step 5, the gradient annealing process is as follows: the membrane that has completed the phosphoric acid solution activation treatment is first treated at 110-120℃ for 1-2 hours to release internal stress, and then treated at 130-140℃ for 1-2 hours to enhance the crosslinking density.

[0015] Another aspect of the present invention provides a proton exchange membrane prepared by the above-described method, the proton exchange membrane comprising a base membrane and sulfonated COF coated on both sides of the base membrane. S The coating, the base film comprising a polybenzimidazole backbone, wherein the sulfonated polybenzimidazole backbone contains zirconium phosphate and amino-functionalized MOF nanoparticles; the zirconium phosphate has a glass network structure.

[0016] In summary, the present invention has the following beneficial effects: 1. The sulfonic acid groups of sulfonated polybenzimidazole can provide a good proton conduction channel, but its hydrophilicity may lead to water absorption and swelling at high temperatures. The preparation method provided in this invention uses sulfonated polybenzimidazole as the main chain and employs a metal-organic framework (MOF) material with a microporous structure. S As an enhancing phase, on the one hand, MOF S The high specific surface area and rigid structure of the SPBI nanofiller, dispersed in the polymer matrix, can restrict the high-temperature movement of SPBI segments, effectively suppress swelling, and the amino-functionalized MOF S The amino group of SPBI forms an acid-base pair with the sulfonic acid group, which can further enhance the interfacial bonding force and reduce the swelling space. Zirconium phosphate is then used to form a glass network structure via a sol-gel method. ZrP possesses a rigid framework, thus effectively suppressing high-temperature swelling and phosphate loss, and MOF... S The crosslinking density of the material, enhanced by zirconium phosphate, can further form a three-dimensional interpenetrating network, more effectively restricting the movement of polymer chains. Therefore, the proton exchange membrane of this invention exhibits a significant effect in suppressing high-temperature swelling, while MOF... S The proton conduction ability of zirconium phosphate can suppress swelling while maintaining proton conduction efficiency; The membrane prepared by the method of this invention achieves low swelling ratio and phosphate retention at high temperature through the synergistic effect of organic-inorganic multiphase processes: MOF S Enhanced crosslinking and mechanical stability, the zirconium phosphate glass network provides a physical barrier and chemical anchoring, while interfacial interactions optimize overall performance. This design improves the durability of the proton exchange membrane while maintaining efficient proton conduction, making it suitable for high-temperature fuel cell applications.

[0017] 2. The proton exchange membrane prepared by this invention is further configured with COF. S Coating, COF SA rigid porous structure is formed, which has better thermal stability than MOF. S The coating provides additional rigid support to the proton exchange membrane, suppressing the chain segment movement of the SPBI backbone at high temperatures and further reducing the swelling rate; and COF S Its covalent structure exhibits better tolerance to acidic environments than some MOFs. S The coating can protect the underlying MOF. S This protects the polymer backbone from acid corrosion, extending the membrane's lifespan. At the same time COF S The addition of a coating, combined with the synergistic effect of MOFs / zirconium phosphate glass network, can form a multi-level pore structure, thereby creating a barrier against phosphate loss: i.e., amino-functionalized MOFs. S The micropores preferentially adsorb small water molecules through size exclusion effect, but allow protons to pass through; while larger phosphate molecules are partially blocked, slowing their diffusion rate; the zirconium phosphate glass network formed by the sol-gel method has a mesoporous structure, filling the MOF. S The gaps between particles reduce pore connectivity, block long-range diffusion paths, and COF S The pore size is slightly larger than that of a phosphoric acid molecule, but dynamic "pore shrinkage" can be achieved through surface sulfonic acid group functionalization, physically intercepting phosphoric acid, and COF S Ordered channels and underlying MOF S The disordered pores of the zirconium phosphate glass network create a "maze effect," significantly extending the diffusion paths of phosphoric acid and water.

[0018] 3. In the preparation method of this invention, after the membrane is formed, it is further activated with phosphoric acid solution. During this process, the MOF in the proton exchange membrane... S micropores and COF S The regular channels of the MOF can fully adsorb phosphoric acid molecules in high-temperature, high-concentration phosphoric acid solutions, i.e., amino-functionalized MOFs. S The pores preferentially capture phosphoric acid through hydrogen bonding and size effects, forming localized high-concentration phosphoric acid regions, COF S The regular channels allow phosphate molecules to be oriented with sulfonic acid or amino groups, forming continuous proton conduction pathways. This significantly increases the phosphate loading, thereby improving the proton conductivity of the composite membrane. Furthermore, the membrane of this invention is immersed in a high-temperature environment, allowing the SPBI backbone to pre-swell and release internal stress. This further reduces the swelling rate during high-temperature operation of the fuel cell, preventing mechanical failure caused by sudden deformation. Further gradient annealing, through a phased strategy of "stress release - pre-crosslinking → deep crosslinking - densification," achieves the following performance leaps: 1) Mechanical strengthening: Increased cross-linking density significantly optimizes swelling resistance and mechanical strength; 2) Conduction-blocking balance: Proton conductivity increases, phosphate loss rate decreases; 3) Long-term stability: The structural stability and chemical anchoring ability are enhanced simultaneously at high temperatures. Attached Figure Description

[0019] Figure 1 This is a photograph of the proton exchange membrane prepared in Comparative Example 2. Detailed Implementation

[0020] The following examples are intended to enable those skilled in the art to more fully understand the present invention, but do not limit the invention in any way.

[0021] Unless otherwise specified, the materials used in the embodiments of the present invention can be obtained commercially or prepared according to conventional methods known to those skilled in the art.

[0022] Example 1 Step 1: Preparation of the composite solution: a) Dissolve 15g SPBI (sulfonation degree of 50%) in 85mL NMP, the concentration of sulfonated polybenzimidazole is 15wt%, stir until completely transparent to obtain a mixed solution; b) Add 5 g of NH2-UiO-66 with a pore size of 1.1 nm to the mixed solution obtained in step a). (NH2-UiO-66 is synthesized by solvothermal reaction in DMF using zirconium salt as the metal source and 2-aminoterephthalic acid as the ligand using existing techniques known to those skilled in the art.) React at 80°C for 12 h under nitrogen protection. During this process, the moisture content of the system is reduced to below 500 ppm by nitrogen replacement method (the process of increasing the vacuum in the flask to ≤100 Pa and then purging nitrogen to atmospheric pressure is repeated more than 3 times). c) Centrifuge at 8000 rpm for 20 min to remove ungrafted MOFs. S A composite solution is obtained; In the above preparation method, NMP, NH2-UiO-66 and SPBI are first pre-dried. The drying method can be a commonly used method in the existing field, such as calcination, nitrogen bubbling, or vacuum drying oven dehydration, so that the water content of the reaction system is <500ppm. Step 2: Preparation of SPBI / ZrP-MOF hybrid sol: 1) 3.63 g of 12 mol ZrOCl2·8H2O was mixed with 0.94 mL of 15 mol H3PO4 and aged for 48 h to obtain zirconium phosphate precursor; 2) Mix 2.78 g of zirconium phosphate precursor with 5 mL of the composite solution obtained in step one; 3) First, add hydrochloric acid to adjust the pH to 1.5, then add ammonia to adjust the pH to 3.0 to form a uniform sol; Step 3: Casting and film formation: The hybrid sol obtained in step 2 was placed in a casting equipment for casting film formation. The casting parameters were: coating speed 30 mm / s, doctor blade gap 350 μm, drying temperature 80℃ for 3 h and then drying at 100℃ for 6 h. Step 4: Preparation of the surface sulfonated COFs coating: A) Mix 1.5 mL of aminosilane (KH-550) with 100 mL of ethanol, add 5 g of SA-TFP COF (pore size 1.8 nm, sulfonic acid group density 2.0 mmol / g) and 0.5 g of PVP dispersant, and sonicate for 1 h to obtain sulfonated COFs slurry; B) Coat both sides of the base film after step three with sulfonated COFs slurry, with a coating thickness of 15 μm on each side, and then pre-dry at 60°C. C) Immerse the membrane from step 2) in ethanol to remove free silane, and then dry it in a vacuum drying oven at 60°C and a vacuum degree ≤10 Pa for 4 hours. Step 5: Phosphoric acid activation treatment: The membrane after step four was immersed in a 75 wt% phosphoric acid solution at 90°C for 1.5 hours to achieve a phosphoric acid doping amount of 220 wt%. Step 6: Gradient annealing: The membrane material after completing step five is subjected to gradient annealing. First, it is treated at 120°C for 2 hours to eliminate internal stress, and then treated at 140°C for 2 hours to enhance the crosslinking density.

[0023] Example 2 Step 1: Preparation of the composite solution: a) Dissolve 10g SPBI (sulfonation degree of 50%) in 90mL NMP, the concentration of sulfonated polybenzimidazole is 10wt%, stir until completely transparent to obtain a mixed solution; b) Add 2 g of NH2-UiO-66 with a pore size of 1.1 nm to the mixed solution obtained in step a), and react at 60 °C for 9 h under nitrogen protection. During this process, the water content in the system is reduced to below 500 ppm by nitrogen replacement method (increasing the vacuum in the flask to ≤100 Pa and then filling it with nitrogen to atmospheric pressure and repeating this process more than 3 times). c) Centrifuge at 7000 rpm for 20 min to remove ungrafted MOFs. S A composite solution is obtained; In the above preparation method, NMP, NH2-UiO-66 and SPBI are first pre-dried. The drying method can be a commonly used method in the existing field, such as calcination, nitrogen bubbling, or vacuum drying oven dehydration, so that the water content of the reaction system is <500ppm. Step 2: Preparation of SPBI / ZrP-MOF S Hybrid sol: 1) 2.42 g of 8 mol ZrOCl2·8H2O was mixed with 1.63 mL of 16 mol H3PO4 and aged for 48 h to obtain zirconium phosphate precursor; 2) Mix 5.48 g of zirconium phosphate precursor with 10.54 mL of the composite solution obtained in step one; 3) First, add hydrochloric acid to adjust the pH to 1.8, then add ammonia to adjust the pH to 2.8 to form a uniform sol; Step 3: Casting and film formation: The hybrid sol obtained in step 2 was placed in a casting equipment for casting film formation. The casting parameters were: coating speed 20 mm / s, doctor blade gap 250 μm, drying temperature 70℃ for 2 h, drying at 90℃ for 4 h, and finally annealing at 120℃ for 1 h. Step 4: Preparation of the surface sulfonated COFs coating: A) Mix 1.25 mL of aminosilane (KH-550) with 98.75 mL of ethanol, add 2 g of SA-TFP COF (pore size 1.5 nm, sulfonic acid group density 1.6 mmol / g) and 0.4 g of PVP dispersant, and sonicate for 1 h to obtain sulfonated COF. S Slurry; B) Complete step three by double-sided coating of the base film with sulfonated COF. S The slurry, with a coating thickness of 10μm on each side, is then pre-dried at 60℃. C) Immerse the membrane obtained from step B) in ethanol to remove free silane, and then dry it in a vacuum drying oven at 60°C and a vacuum degree ≤10 Pa for 4 hours. Step 5: Phosphoric acid activation treatment: The membrane after step four was immersed in a 70 wt% phosphoric acid solution at 80°C for 1.5 hours to achieve a phosphoric acid doping concentration of 200 wt%. Step 6: Gradient annealing: The membrane after completing step five is subjected to gradient annealing. First, it is treated at 115℃ for 1.5h to eliminate internal stress, and then treated at 135℃ for 1.5h to enhance the crosslinking density.

[0024] Example 3 Step 1: Preparation of the composite solution: a) Dissolve 5g SPBI (sulfonation degree of 50%) in 80mL NMP, the concentration of sulfonated polybenzimidazole is 5wt%, stir until completely transparent to obtain a mixed solution; b) Add 1.5 g of NH2-MIL-125(Ti) with a pore size of 0.9 nm to the mixed solution obtained in step a). (NH2-MIL-125(Ti) is synthesized by reacting tetraisopropyl titanate and 2-aminoterephthalic acid in methanol solvent using existing techniques known to those skilled in the art.) React at 30°C for 6 h under nitrogen protection. During this process, the moisture content in the system is reduced to below 500 ppm by nitrogen replacement method (the process of increasing the vacuum in the flask to ≤100 Pa and then purging nitrogen to atmospheric pressure is repeated more than 3 times). c) Centrifuge at 5000 rpm for 12 min to remove ungrafted MOFs. S A composite solution is obtained; In the above preparation method, NMP, NH2-MIL-125(Ti) and SPBI are first pre-dried. The drying method can be a common method in the existing field, such as calcination, nitrogen bubbling, or vacuum drying oven dehydration, so that the water content of the reaction system is <500ppm. Step 2: Preparation of SPBI / ZrP-MOF hybrid sol: 1) Mix 5.04 g of 4 mol ZrOCl2·8H2O with 1.63 mL of 12 mol H3PO4 and age for 48 h to obtain zirconium phosphate precursor; 2) Mix 4.27 g of zirconium phosphate precursor with 20.2 mL of the composite solution obtained in step one; 3) First add hydrochloric acid to adjust to pH 2, then add ammonia to adjust to pH 2.5 to form a uniform sol; Step 3: Casting and film formation: The hybrid sol obtained in step 2 was placed in a casting equipment for casting film formation. The casting parameters were: coating speed 10 mm / s, doctor blade gap 150 μm, drying temperature 65 ℃ for 1.5 h, drying at 85 ℃ for 3 h, and finally annealing at 120 ℃ for 1 h. Step 4: Preparation of the surface sulfonated COFs coating: A) Mix 1 mL of aminosilane (KH-550) with 99 mL of ethanol, add 1 g of SO3H-COF-300 (pore size 0.8 nm, sulfonic acid group density 3 mmol / g) and 0.4 g of PVP dispersant, and sonicate for 1 h to obtain sulfonated COF. S Slurry; B) Complete the double-sided coating of the base film from step three with sulfonated COF. S The slurry, with a coating thickness of 5μm on each side, is then pre-dried at 60℃. C) Immerse the membrane obtained from step B) in ethanol to remove free silane, and then dry it in a vacuum drying oven at 60°C and a vacuum degree ≤10 Pa for 4 hours. Step 5: Phosphoric acid activation treatment: The membrane after step four was immersed in a 65 wt% phosphoric acid solution at 80°C for 0.5 h to achieve a phosphoric acid doping concentration of 180 wt%. Step 6: Gradient annealing: The membrane after completing step five is subjected to gradient annealing. First, it is treated at 110°C for 1 hour to eliminate internal stress, and then treated at 130°C for 1 hour to enhance the crosslinking density.

[0025] Comparative Example 1 Comparative Example 1 was prepared using the same method as in Example 1, except that no amino-functionalized MOF was added. S The nanoparticles undergo a grafting reaction. Steps one and two are modified, while the remaining parameters are the same as in Example 1. The specific steps of steps one and two are as follows: Step 1: Prepare SPBI solution: Dissolve 15g of SPBI (sulfonation degree of 50%) in 85mL of NMP, the concentration of sulfonated polybenzimidazole is 15wt%, and stir until completely transparent to obtain SPBI solution; Step 2: Preparation of SPBI / ZrP-MOF hybrid sol: 1) Mix 3.63 g of 12 mol ZrOCl2·8H2O with 0.83 mL of 15 mol H3PO4 and age for 48 h to obtain zirconium phosphate precursor; 2) Mix the zirconium phosphate precursor with the SPBI solution obtained in step one; 3) First, add hydrochloric acid to adjust the pH to 1.5, then add ammonia to adjust the pH to 3.0 to form a uniform sol.

[0026] Comparative Example 2 Comparative Example 2 follows the same preparation method as Example 1, except that it does not use a zirconium phosphate glass network, steps one and two are omitted, i.e., the composite solution obtained in step one is placed in a casting apparatus for casting film formation. All other parameters are the same as in Example 1. The specific steps of step one are as follows: a) Dissolve 15g SPBI (sulfonation degree of 50%) in 85mL NMP, the concentration of sulfonated polybenzimidazole is 15wt%, stir until completely transparent to obtain a mixed solution; b) Add 5 g of NH2-UiO-66 with a pore size of 3.4 nm to the mixed solution obtained in step a), and react at 80 °C for 12 h under nitrogen protection. During this process, the water content in the system is reduced to below 500 ppm by nitrogen replacement method (the process of increasing the vacuum in the flask to ≤100 Pa and then filling it with nitrogen to atmospheric pressure is repeated more than 3 times). c) Add 1.14 g PVP to increase viscosity, and mechanically stir at 500 rpm for 1 h to ensure complete dissolution of PVP; d) Centrifuge at 8000 rpm for 20 min to remove ungrafted MOFs. S Obtain MOF S A composite solution with a loading of 25 wt%.

[0027] Comparative Example 3 Comparative Example 3 was prepared using the same method as in Example 1, except that no sulfonated COF was used. S For the coating, step four is omitted; that is, after casting and drying in step three, the phosphoric acid activation treatment is performed directly. The remaining parameters are the same as in Example 1.

[0028] Comparative Example 4 Comparative Example 4 follows the same preparation method as Example 1, except that it does not undergo phosphoric acid solution activation treatment and omits step four, namely step four, sulfonation of COF. S Gradient annealing was performed after coating, and the remaining parameters were the same as in Example 1.

[0029] Comparative Example 5 Comparative Example 5 was prepared using the same method as Example 1, except that a single-stage annealing process was used, and the annealing parameters in step six were changed to 130°C for 2 hours. The remaining parameters were the same as in Example 1.

[0030] Test Example 1 The membranes of Examples 1-3 and Comparative Examples 1-5 were subjected to performance tests: the proton conductivity was tested using an electrochemical impedance spectroscopy (EIS) system at a test temperature of 120°C and a humidity of 80% RH; the gas permeability was detected using a gas permeation analyzer; the membrane samples were subjected to constant temperature treatment in a high-temperature oven (150°C, 24h), and the swelling rate was detected by measuring the dimensional changes of the membrane before and after immersion using a laser thickness gauge; the phosphoric acid retention rate was tested using a thermogravimetric analyzer (TGA) or gravimetric analysis.

[0031] The test results are shown in Table 1. Table 1

[0032] Comparative Example 1: MOF without amino-functionalized elements S When nanoparticles undergo grafting reactions, the lack of high-density phosphate anchoring sites and the physical confinement of MOF pores leads to increased migration of SPBI segments at high temperatures, resulting in significant high-temperature swelling and easy loss of phosphate.

[0033] Comparative Example 2, a zirconium phosphate-free glass network, lacks the structural confinement of a rigid ZrP framework. Therefore, at high temperatures, the chain segment movement of the base film intensifies, leading to increased free volume diffusion of phosphate molecules. This results in the film easily swelling and phosphate loss. Figure 1 As shown.

[0034] Comparative Example 3: Uncoated COF S The layer leads to a lack of regular channels and dynamic barrier of sulfonic acid groups on the membrane surface, resulting in increased hydrogen permeability and rapid diffusion of phosphoric acid molecules along the disordered channels, leading to a decline in performance.

[0035] Comparative Example 4 did not undergo phosphoric acid solution activation treatment. This meant that the SPBI backbone was not pre-swollen through phosphoric acid activation, leading to MOF... S Micropores and COF S The channels were not fully filled with phosphoric acid, the proton transport path was discontinuous, and the chain segment relaxation of the base film was aggravated at high temperature. Therefore, the proton conductivity and phosphoric acid retention of Comparative Example 4 were relatively poor.

[0036] Comparative Example 5 uses single-stage high-temperature annealing, which leads to the concentrated release of internal stress in the SPBI main chain and zirconium phosphate network. That is, the residual stress is difficult to eliminate and the cross-linking density is insufficient. Therefore, microcracks and significant swelling are likely to occur at high temperatures, resulting in decreased durability.

[0037] This specific embodiment is merely an explanation of the present invention and is not intended to limit the invention. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they are within the scope of the claims of the present invention.

Claims

1. A method for preparing a proton exchange membrane, characterized in that: Includes the following steps: Step 1: Dissolve sulfonated polybenzimidazole in N-methylpyrrolidone, add amino-functionalized MOF nanoparticles for grafting reaction to obtain composite solution; Step 2: The zirconium phosphate precursor solution is mixed with the composite solution obtained in Step 1 using the sol-gel method. The pH is adjusted to 1.5-2.0 with hydrochloric acid, and then adjusted to 2.5-3.0 with ammonia to form SPBI / ZrP-MOFs hybrid sol. Step 3, use the SPBI / ZrP-MOF obtained in Step 2. S The hybrid sol is cast into a film and then dried; Step 4: Form sulfonated COF on both sides of the membrane. S The coating is then dried. Step 5: The membrane obtained in Step 4 is first activated with phosphoric acid solution and then subjected to gradient annealing to obtain the proton exchange membrane.

2. The preparation method according to claim 1, characterized in that: Step 1 is as follows: a) Sulfonated polybenzimidazole is dissolved in N-methylpyrrolidone to obtain a mixed solution; the concentration of sulfonated polybenzimidazole in the mixed solution is 5-15 wt%. b) Add amino-functionalized MOF to the mixed solution obtained in step a). S Nanoparticles were reacted at 30-80℃ for 6-12 hours under nitrogen protection. c) The composite solution obtained after centrifugation; In step b), the sulfonated polybenzimidazole and amino-functionalized MOF S The mass ratio of nanoparticles is (3:1)-(10:1), and the water content of the reaction system is controlled to be <500ppm.

3. The preparation method according to claim 2, characterized in that: In step a), the degree of sulfonation of the sulfonated polybenzimidazole is 30%-50%; In step b), the amino-functionalized MOF nanoparticles are selected from at least one of NH2-UiO-66 and NH2-MIL-125(Ti), and their pore size is 0.6-1.6 nm.

4. The preparation method according to claim 1, characterized in that: Step 2 consists of the following steps: 1) Mix ZrOCl2·8H2O and H3PO4 at a molar ratio of 1:1.25-1:3 and age for 24-48 h to obtain a zirconium phosphate precursor solution; 2) Mix the zirconium phosphate precursor solution with the composite solution obtained in step 1 at a mass ratio of sulfonated polybenzimidazole to zirconium phosphate precursor of (1:0.5)-(1:4); 3) First, add hydrochloric acid to adjust the pH to 1.5-2.0, then add ammonia to adjust the pH to 2.5-3.0, forming SPBI / ZrP-MOF. S Hybrid sol.

5. The preparation method according to claim 1, characterized in that: In step 4, the sulfonated COF S The coating formation steps are as follows: A) Mix the silane coupling agent with ethanol, and add sulfonated COF. S Polyvinylpyrrolidone (PVP) was added as a dispersant, and after ultrasonic-assisted dispersion, a mixed slurry was obtained; the volume ratio of the silane coupling agent to ethanol was 1-1.5:100, and the concentration of PPVP in the mixed slurry was 0.4-0.6 wt%. B) Coat both sides of the membrane with the mixed slurry obtained in step A); C) Immerse the membrane from step B) in ethanol and then dry it.

6. The preparation method according to claim 5, characterized in that: In step A), the sulfonated COF S It is at least one of SO3H-COF-300, SA-TFP COF, and SO3H-COF-316, wherein the pore size of SA-TFP COF is 1.2-1.8 nm and the sulfonic acid group density is 1.2-2.0 mmol / g, and the pore size of SO3H-COF-300 and SO3H-COF-316 is 0.65-1.0 nm and the sulfonic acid group density is 2.8-4.2 mmol / g. The silane coupling agent is an aminosilane.

7. The preparation method according to claim 5, characterized in that: In step B), the coating thickness is 5-15 μm.

8. The preparation method according to claim 1, characterized in that: In step 5, the phosphoric acid solution activation treatment is performed by immersing the obtained membrane in a phosphoric acid solution at 80-90°C for 0.5-1.5 hours. The concentration of the phosphoric acid solution is 65-75 wt%.

9. The preparation method according to claim 1, characterized in that: In step 5, the gradient annealing process is as follows: the membrane that has been activated by phosphoric acid solution is first treated at 110-120℃ for 1-2 hours, and then treated at 130-140℃ for 1-2 hours.

10. A proton exchange membrane prepared by the method according to any one of claims 1-9, characterized in that: The proton exchange membrane comprises a base membrane and sulfonated COF coated on both sides of the base membrane. S The coating, the base film comprising a polybenzimidazole backbone, wherein the sulfonated polybenzimidazole backbone contains zirconium phosphate and amino-functionalized MOF nanoparticles; the zirconium phosphate has a glass network structure.